Association of electrocardiogram alterations of rescuers and performance during a simulated cardiac arrest: A prospective simulation study. - Lucas Tramèr; Christoph Becker; Seraina Hochstrasser; Stephan Marsch; Sabina Hunziker (PLoS ONE)
Background Performance of cardiopulmonary resuscitation (CPR) causes significant mental stress for rescuers, especially if performed by inexperienced individuals. Our aim was to study electrocardiogram (ECG) alterations in rescuers and its association with gender and CPR performance. Methods We included 126 medical students in this prospective, observational simulator study. Each student was equipped with a 3-lead continuous ECG device tracking the individual electrocardiographic output before, during and after CPR. We analyzed variations in heart rate, heart-rate variability (HRV) and ST- and T-wave morphology. Results Compared to baseline, mean heart rate (bpm) significantly increased during resuscitation and again decreased after resuscitation (from 87 to 97 to 80, p<0.001). Heart-rate variability (the standard deviation of all N-N intervals, SDNN) (ms2) showed the opposite pattern, decreasing during resuscitation and increasing after resuscitation (117 to 92 to 93ms, p<0.001). Abnormalities in T-waves and ST-segments were observed in 29.4% of participants. Maximal heart rate (r = 0.25, p = 0.046) as well as heart rate reactivity (r = 0.7, p<0.001) correlated with hands-on time, a measure of CPR performance. Compared to males, female rescuers had a significantly higher maximal heart rate (136bpm vs. 126bpm, p = 0.008) and lower HRV (SDNN 102 vs. 119ms, p = 0.004) and tended to show more abnormalities in T-waves and ST-segments (36% vs. 21%, p = 0.080). Conclusion CPR causes significant ECG alterations in healthy medical students with ST-segment and T-wave abnormalities, with more pronounced effects in females. Clinical implications of these findings need to be further investigated.